2020
DOI: 10.3390/nano10061234
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Therapeutic Approach for Diabetic Wound Healing

Abstract: Diabetes mellitus (DM) is a common endocrine disease characterized by a state of hyperglycemia (higher level of glucose in the blood than usual). DM and its complications can lead to diabetic foot ulcer (DFU). DFU is associated with impaired wound healing, due to inappropriate cellular and cytokines response, infection, poor vascularization, and neuropathy. Effective therapeutic strategies for the management of impaired wound could be attained through a better insight of molecular mechanism and pathophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 159 publications
(187 reference statements)
0
63
0
1
Order By: Relevance
“…Currently, there are some technologies of wound healing treatment for diabetes, namely topical drug treatment (eg, drugs, peptides and growth factors), cellular therapies (eg, stem cells and fibroblasts) and biomaterial-based treatment. 39 Biomaterials with controlled-release of signaling molecules can be combined with other therapeutic methods, which is a promising treatment method for diabetic wound healing. 40 In this review, we will summarize biomaterials and their potential applications in diabetic wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are some technologies of wound healing treatment for diabetes, namely topical drug treatment (eg, drugs, peptides and growth factors), cellular therapies (eg, stem cells and fibroblasts) and biomaterial-based treatment. 39 Biomaterials with controlled-release of signaling molecules can be combined with other therapeutic methods, which is a promising treatment method for diabetic wound healing. 40 In this review, we will summarize biomaterials and their potential applications in diabetic wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oxidative stress, which is known to be increased in diabetic wound healing, may lead to a stronger inflammatory response or a longer-lasting inflammatory phase (Luc et al, 2017;Cano-Sanchez et al, 2018;Kim et al, 2019). However, a reduction in, or impaired activity of, antioxidant molecules may also be the cause of impaired wound healing in diabetes (Ezhilarasu et al, 2020). NAC is an acetylated cysteine derivative that can help to protect cells against oxidative damage, and has been shown to modulate oxidative stress and inflammation in several ways (Janeczek et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The integration of nanotechnology and targeted drug delivery has opened potential avenues to achieve this goal. With high surface area to volume ratios and unique physiochemical properties, the architecture of nanoparticles allows optimization for the delivery of various imaging and therapeutic agents 4 .…”
Section: Introductionmentioning
confidence: 99%